ISSUES OF EFFICIENT LAND USE IN KARAKALPAKISTAN'S WATER SHORTAGE - Reimov Nietbay; Utepbergenova Venera; Reymov Ómirbay; Xudaybergenova Nilufar; Reymova Feruza (Web of Journals Publishing, 2025)
In recent years, the process of land degradation in the Republic of Karakalpakstan is intensifying. The main reasons for this are the shortage of water, the decrease in water demand for agriculture by 39-41% in 1999-2001, by 50-55% in 2007-2010, and by 54-58% in recent years. pouring, worries humanity.